Association of mRNA Expression Level of IP-10 in Peripheral Blood Mononuclear Cells with HBV-associated Acute-on-chronic Liver Failure and Its Prognosis - 王晓霖;陈秀记;叶海辉;邢凌翔;韩晓颖;程正江;黄少军 (Current medical science, 2017)
HBV-associated acute-on-chronic liver failure is prevalent in mainland China. The prognosis of HBV-ACLF is poor. The mortality of HBV-ACLF is approximately 80%. Therefore, a prognostic indicator was needed in order to allow us to intervene as soon as possible. The model for end-stage liver disease（MELD） scoring system is widely used to predict the prognosis of liver failure. However, the assessment is too complex to restrict its application. This study aimed to investigate the expression of IP-10 in peripheral blood mononuclear cells（PBMC）, in order to explore the relationship between the expression and prognosis of patients with HBV-ACLF. The mRNA level of IP-10 in PBMCs were analyzed in 80 patients with HBV-ACLF, 40 patients with chronic hepatitis B（CHB） and 40 healthy people by fluorescent quantitative PCR. IP-10 mRNA level was significantly higher in the HBV-ACLF group than in the other two groups（P〈0.01）. Group with MELD score below 30 had lower IP-10 mRNA level than group with MELD score over 30（P〈0.05）. The IP-10 mR NA level in PBMCs in positive group was higher than that in negative group（P〈0.01）. With a threshold of 0.925, the area under the receiver operating characteristic（ROC） curves was 0.815. These findings suggest that assessment of IP-10 mRNA level in the PBMCs would be helpful for evaluating the disease severity and prognosis in patients with HBV-ACLF.